Independent Infinitive in Directive Speech Acts for Direct Communication in the Polish Language and Its Equivalents in the French Language - Górnikiewicz, Joanna (Taikomoji kalbotyra, 2021)
This article discusses the Polish independent infinitive, which constitutes a predicate in imperative utterances, and its French functional equivalents. The analysis was conducted at two levels. In the first part, the author describes the independent infinitive in the Polish language referring to the Polish formal structural syntax (Saloni, Świdziński 2012). This is to determine which place is occupied by this unit in a sentence, both in relation to other uses of the infinitive and in comparison to other units with the function of a predicate in statements of the same modality. The French structural equivalent has been determined on the basis of the same criterion of syntax dependency. However, even though both languages have corresponding structures, they do not use them in the same way. Only in Polish it is possible to form sentences with infinitive predicates in the spoken language, in face-to-face conversation. What are the factors that favour choosing this form? The author answers this question in her semantic and pragmatic analysis, conducted in the methodological framework of speech act theory (Searle 1979, Vanderveken 1988). She presents imperatives as a class of speech acts, which are extensively developed and specifies those, which can be executed by means of utterances with infinitive predicates. Additionally, factors of social and psychological character have been taken into consideration, as those which favour selecting the discussed form. What structure constitutes its functional equivalent in the French language? An analysis of a body composed of examples originating primarily from dialogues in contemporary literary works and their approved translations has allowed, on the one hand, to confirm the intuitive belief that grammar forms perform this function, in face-to-face oral communication the French language has only the command mode forms (l’impératif in French). On the other hand, we can launch a discussion about possibilities to translate them into a language which does not allow for an analogous use of the available infinitive structure.
Keywords: independent infinitive; command mode forms; syntax; injunction; speech acts; contrastive grammar